Extracellular vesicles regulate the transmission of insulin resistance and redefine noncommunicable diseases - Li, Biao; Li, Wan; Liu, Tiancai; Zha, Longying (Frontiers in Molecular Biosciences, 2023)
Non-communicable diseases (NCD) are considered unable to transmit directly from one person to another, such as diabetes and related neurological disorders. However, NCD may be transmissible in vivo through extracellular vesicles (EVs). A long-term high-fat diet (HFD) can induce a series of health issues like hyperlipidemia, type 2 diabetes mellitus (T2DM), and diabetic peripheral neuropathy (DPN) due to insulin resistance. Multiple molecular signaling changes can stimulate insulin resistance, especially blocking insulin signaling by increased insulin resistance inducer (phosphorylation of negative regulatory sites of IRS) and decreased tyrosine phosphorylation of insulin receptor substrate ( phosphorylation of positive regulatory sites of IRS), thus leading to reduced phosphorylation of AKT. Current prevention and treatments of T2DM and its complications mainly focus on improving insulin sensitivity, enhancing insulin secretion, or supplementing exogenous insulin based on a common assumption that insulin resistance is non-communicable. Insulin resistance is transmissible within multiple tissues or organs throughout the body. Exploring the regulatory roles of EVs in developing insulin resistance may provide us with novel and effective preventive and therapeutic strategies.